2020
DOI: 10.1192/bjo.2020.16
|View full text |Cite|
|
Sign up to set email alerts
|

Australian Indigenous model of mental healthcare based on transdiagnostic cognitive–behavioural therapy co-designed with the Indigenous community: protocol for a randomised controlled trial

Abstract: Background A four- to seven-fold increase in the prevalence of current mood, anxiety, substance use and any mental disorders in Indigenous adults compared with non-Indigenous Australians has been reported. A lifetime prevalence of major depressive disorder was 23.9%. High rates of comorbid mental disorders indicated a transdiagnostic approach to treatment might be most appropriate. The effectiveness of psychological treatment for Indigenous Australians and adjunct Indigenous spiritual and cultural healing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In Australia, Aboriginal and Torres Strait Islander people were found to have incidence rates for anxiety and any mental disorder that are 3 times and 4 times higher, respectively, than the non-Indigenous population (Nasir et al, 2018). In 2020, a randomized controlled trial of a mental health intervention in four Aboriginal communities produced promising results that could inform future guidelines and treatment and care programs (Toombs et al, 2020). In New Zealand, Māori peoples also experience higher rates of poor mental health compared to non-Māori people in New Zealand (Baxter et al, 2006).…”
Section: Implications For Indigenous Peoples In Other Countriesmentioning
confidence: 99%
“…In Australia, Aboriginal and Torres Strait Islander people were found to have incidence rates for anxiety and any mental disorder that are 3 times and 4 times higher, respectively, than the non-Indigenous population (Nasir et al, 2018). In 2020, a randomized controlled trial of a mental health intervention in four Aboriginal communities produced promising results that could inform future guidelines and treatment and care programs (Toombs et al, 2020). In New Zealand, Māori peoples also experience higher rates of poor mental health compared to non-Māori people in New Zealand (Baxter et al, 2006).…”
Section: Implications For Indigenous Peoples In Other Countriesmentioning
confidence: 99%
“…The IMMHC has been developed as a model of mental health care that is both effective and readily embraced by Indigenous people, which will be fundamental for its successful uptake and sustainability. Indigenous‐led design and development of a treatment model of mental health care will also guarantee empowerment, adaptability and transferability 26 . The outcomes from this study provide an essential overview to inform participants lived experiences towards the development of the IMMHC.…”
Section: Discussionmentioning
confidence: 94%
“…From these studies, major depressive disorder was identified as the issue most prevalent among Indigenous adults 4 . As a result, a randomised controlled trial (RCT) to design and develop an Indigenous Model of Mental Health Care (IMMHC) 26 for the treatment of depression was designed.…”
Section: Objectivementioning
confidence: 99%
“…Modern Western psychotherapies such as CBT, ACT, and CFT are largely based on a set of evidence-based psychological principles that are considered to be generally applicable to human suffering. However, it is also well recognized that for these therapies to be effective in Indigenous (Nelson et al, 2014;Toombs et al, 2020) or other cultural contexts (Rathod and Kingdon, 2009;Iwamasa and Hays, 2019), they need to be culturally responsive. Moreover, in order to be culturally responsive, community engagement processes such as co-design workshops and reference groups with key stakeholders over an extended period of time are required (Singer et al, 2015;Toombs et al, 2020).…”
Section: Discussionmentioning
confidence: 99%